The Early Bronze Age Bowls from Dagestan Coastal Area (Typology, Décor and Chronology Issues) - Arsen L. Budaichiev (Нижневолжский археологический вестник, 2022)
The article is devoted to the ceramic bowls study being one of the most exemplary earthenware categories presented in rather large numbers on the Early Bronze Age sites of Dagestan coastal area. The main goal of the study is to develop a typology of the bowls from the settlements (Gheme-tyube I, II, Kabaz-kutan I, II, Torpakh-kala, Ullu-Achi) and the burial grounds (Velikent I, catacomb 8, Velikent II, catacomb 1, Velikent III, catacomb 1, Karabudakhkent II, Kayakent VI) of the region as well as to examine the decor and chronology. According to the shape of the corpus, two main types of bowls are distinguished: type I – bowls in the form of an inverted truncated cone with straight or slightly oval sides at the top; type II – bowls with rounded sides and a slightly everted rim. Type I bowls in the shape of a rim are divided into four subtypes (A, B, C, D). Type II bowls do not have clear varieties. For each type and subtype of the bowls, analogies and parallels are given not only from the regions adjacent to Dagestan, but also from other areas (Eastern and Central Anatolia, Northwestern Iran, etc.), where the Kuro-Arak culture are also widespread. The article identifies common and rare types and subtypes of bowls based on typological analysis and statistical calculations. The paper also deals with the decoration of the bowls which is an episodic phenomenon for them (mortise ornament along the inner edge of the bowl, indented decor). An attempt was made to study the chronology of the bowls, the allocation of early and later types and subtypes on the basis of the monuments’ dating, stratigraphic observations and a series of radiocarbon dating.